Risk of hospital admission for liver injury in users of NSAIDs and nonoverdose paracetamol: Preliminary results from the EPIHAM study. Issue 11 (16th August 2018) - Gulmez, Sinem Ezgi; Unal, Ulku Sur; Lassalle, Régis; Chartier, Anaïs; Grolleau, Adeline; Moore, Nicholas
Abstract: Purpose: The SALT study found similar per‐user risks of acute liver failure (ALF) leading to transplantation (ALFT) between NSAIDs and a threefold higher risk in nonoverdose paracetamol (NOP) users. The objective of EPIHAM was to identify the risks of hospital admission for acute liver injury (ALI) associated with NSAIDs and NOP. Methods: Case‐population study in the 1/97 sample of the French population claims database. Acute liver injury was identified from hospital discharge summaries, from 2009 to 2013. Exposure for cases was dispensing of NSAID or NOP resulting in exposure within 30 days before admission. Population exposure was the number of patients using the drugs over the study timeframe and total number of DDD dispensed. Results: Of 63 cases of ALI, 13 had been exposed to NSAIDs and 24 to NOP. Events per million DDD (95% CI) ranged from 0.46 (0.09‐1.34) (ketoprofen) to 1.43 (0.04‐7.97) (diclofenac combinations), 0.43 (0.23‐0.73) all NSAIDs combined, 0.58 (0.37‐0.86) for NOP. There was no association with average duration of treatment. Per patient risk ranged from 19.5 (5.31‐49.9) (ibuprofen) per million users to 37.2 (19.8‐63.6) all NSAIDs combined, 58.0 (37.2‐86.3) for NOP. There was a linear relationship between average treatment duration and per‐user risk ( R 2  = 0.51, P  < .05 for NSAIDs, R 2  = 0.97, P  < .01 for NOP). Conclusions: Risk of hospital admission for ALI with NSAIDs and NOP was similar and indicative of a dose and duration‐related effect (pharmacological) effect. Acute liver injury rates were not predictive of ALFT risk.